2013
DOI: 10.1136/bmj.f5980
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive versus invasive respiratory support in preterm infants at birth: systematic review and meta-analysis

Abstract: Objective To assess the role of nasal continuous positive airway pressure (CPAP) initiated at birth for prevention of death and bronchopulmonary dysplasia in very preterm infants. Design Systematic review.Data sources PubMed, Embase, the Cochrane Central Register of Controlled Trials, and online Pediatric Academic Society abstracts from the year of inception to June 2013.Eligibility criteria for selecting studies Randomised controlled trials evaluating the effect of nasal CPAP compared with intubation in prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
312
2
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(328 citation statements)
references
References 24 publications
3
312
2
11
Order By: Relevance
“…It is used in several clinical circumstances and it includes different modes that can be applied. A recent meta-analysis performed by Schmolzer et al showed that nCPAP initiated in the delivery room compared with intubation reduces death or bronchopulmonary dysplasia in very preterm babies [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in several clinical circumstances and it includes different modes that can be applied. A recent meta-analysis performed by Schmolzer et al showed that nCPAP initiated in the delivery room compared with intubation reduces death or bronchopulmonary dysplasia in very preterm babies [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that there was no clear demonstration of a reduction of bronchopulmonary dysplasia (BPD) with the use of noninvasive ventilation [7][8][9][10]. However, recent meta-analysis made by Schmolzer [11] and Fischer [12] demonstrated that there is a statistically significant advantage in the use of non-invasive ventilation regarding death and BPD.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, this is an important distinction to make, as overall the neonatal community seems to be moving toward increased use of NIV, which has shown clinical benefit. 5 A time-based definition of failure has its own disadvantages, as some infants continue to "fail" even after the defined study period, 51 especially the extreme preterm group.…”
Section: Figurementioning
confidence: 99%
“…More recently, randomized controlled clinical trials have established the benefits of primary noninvasive ventilation (NIV) support, especially for nasal continuous positive airway pressure (nCPAP) 3,4 when compared with MV. 5 After extubation from MV, nCPAP is already established as an effective mode of support. 6 Other modes of NIV in preterm infants include bilevel nCPAP (BiPAP)/noninvasive positive pressure ventilation (NIPPV) and heated humidified high-flow nasal cannula (HHHFNC) therapy.…”
mentioning
confidence: 99%
“…Whilst the latest guidance supports the use of nasal Continuous Positive Airway Pressure (CPAP), (1,2) with evidence of improved outcomes compared with routine invasive respiratory support, (3,4) we recently demonstrated the feasibility of the use of nasal high flow (nHF) in the stabilisation of premature babies (23 to 29+6 weeks gestation) in the delivery room prior to transfer to Neonatal Intensive Care Unit (NICU). (5) Although several large studies have previously demonstrated that nHF is generally as effective as nCPAP for postextubation support, (6)(7)(8) there remains a paucity of literature on the use of nHF in the DR. Our previous study showed that stabilisation on nHF reduced the rate of DR intubation and surfactant administration compared to our prior practice.…”
Section: Introductionmentioning
confidence: 99%